Maximize business profits through e-partnerships - Zhao, Fang, 1956- (Hershey PA : IRM Press, 2006)
'This book gives a comprehensive introduction of the concepts and practices of e-partnering and discusses the application of e-partnership in e-commerce, e-business, the supply chain and e-supply chains'--Provided by publisher
Includes bibliographical references and index
Keywords: Electronic commerce; Strategic alliances (Business)